2019
DOI: 10.1186/s41984-018-0026-3
|View full text |Cite
|
Sign up to set email alerts
|

Posterior short-segment fixation with implanting pedicle screw in the fractured level as a feasible method for treatment of thoracolumbar fracture

Abstract: Background: The thoracolumbar spine is vulnerable to fracture in falls or motor vehicle accidents. Thoracolumbar spine fracture can be associated with neurological deficits, long-term pain and disability. The optimal management for these injuries remains a considerable subject for research. Objectives: To evaluate short-term surgical and functional outcome of posterior short-segment fixation with implanting pedicle screw in the fractured level (short same-segment fixation) for treatment of recent single-level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…5 Similar results have been reported by Adawi et al in their study of 36 patients. 18 The mean correction of kyphotic angle was from 33 degrees preoperatively to 12.8 degrees immediate post operatively and 17.1 degrees at 1 year follow-up. Two patients had implant failure in our study with a failure rate of 6.66%.…”
Section: Discussionmentioning
confidence: 87%
“…5 Similar results have been reported by Adawi et al in their study of 36 patients. 18 The mean correction of kyphotic angle was from 33 degrees preoperatively to 12.8 degrees immediate post operatively and 17.1 degrees at 1 year follow-up. Two patients had implant failure in our study with a failure rate of 6.66%.…”
Section: Discussionmentioning
confidence: 87%
“…12,13 Regarding surgical interventions, our study recorded an average blood loss of 187 ± 34.35 ml, which was comparatively lower than the mean operative blood losses reported in other studies, ranging from 351.4 ml to 750 ml. 12,14,15 This could be due to number of reasons like operative techniques followed, medications used or methods of calculating blood loss and more.…”
Section: Discussionmentioning
confidence: 99%
“…7 Low lumbar fractures are relatively uncommon injuries that are anatomically and biomechanically different from fractures of the neighboring thoracolumbar region (T10-L2). Multiple studies have reported on the thoracolumbar [8][9][10][11][12][13] and lumbosacral region, 14 but few studies exist specifically regarding the lower lumbar region. Previous literature reports these fractures are predominant in combat-related spine injuries in US military conflicts.…”
Section: Discussionmentioning
confidence: 99%